Ionic liquids as entrainers - S. A. Reshetov; A. K. Frolkova (Тонкие химические технологии, 2009)
In this article presents the review of modern articles about experimental research and modeling of phase equilibrium of liquid – vapor and liquid – liquid in binary and triple component mixtures that are formed by ionic liquids with various organic substances and also application of ionic liquids in separation processes.